Introduction to Basic Measurement Tools to Support Science Learning at SD Negeri 9 Dewantara - Arlin Maya Sari; Ucia Mahya Dewi; Wulanda; Syafrizal; Desy Sary Ayunda (PT FORMOSA CENDEKIA GLOBAL, 2023)
Community service activities have been carried out at SD Negeri 9 Dewantara. This service program aims to introduce basic measuring tools to improve and support student science learning which starts from grade IV of Elementary School. The basic measuring tool introduced is the measuring tool for length. The material presented includes names, functions and how to use ruler measuring instruments, calipers, and screw micrometers. The introduction of measuring instruments with the inquiry method or direct practice is proven to improve students' science process skills. This is because students are actively involved in every learning process.